Investors Perception About Cash Conversion Cycle When Valuing Firm (A study of Textile Sector of Pakistan Stock Exchange). (KASBIT Business Journal, 2022)
E Efficient management of the cash conversion cycle and its impact on firm value in the textile sector of the Pakistan Stock Exchange is the main purpose of this paper. Liquidity management plays a key role in the valuation of a firm as it affects firm performance in the short and long term. In this paper, we collected data on the textile sector of the Pakistan Stock Exchange from 2012 to 2017. In this paper, we empirically tested different performance measurement proxies like return on equity, return on assets, return on capital employed, and market value (Tobin’s Q). We also used different proxies of leverage as observed during the study of Pakistani companies like long-term debt to equity, total debt to total assets, and debt to capital. We found that the cash conversion cycle and working capital have an impact on market value compared to all other book values taken as a proxy for performance. Results confirm our understanding that investors consider before valuing any firm's liquidity management.